2014
DOI: 10.1007/s00264-014-2346-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical procedures in femoral neck fractures in Finland: a nationwide study between 1998 and 2011

Abstract: Purpose For femoral neck fractures, recent scientific evidence supports cemented hemiarthroplasty (HA) over uncemented HA and suggests that total hip arthroplasty (THA) should be performed more frequently. We report the current surgical trends in treating femoral neck fractures in Finland. Methods The study was conducted using the Finnish National Hospital Discharge Register and included all Finns at least 50 years of age who underwent surgery for femoral neck fractures from 1998 through 2011. Age-and sex-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 34 publications
(41 reference statements)
2
13
0
Order By: Relevance
“…Studies addressing hip fractures report cohort characteristics comparable to those of our study, with a greater proportion of women and a similar proportion of comorbidities.…”
Section: Discussionsupporting
confidence: 63%
“…Studies addressing hip fractures report cohort characteristics comparable to those of our study, with a greater proportion of women and a similar proportion of comorbidities.…”
Section: Discussionsupporting
confidence: 63%
“…In Finland, the likelihood that a patient over the age of 50 with a displaced femoral neck fracture would be treated with THA nearly doubled between 2005 and 2011. 20 Between 2006 and 2011 in South Korea, there was an increase in the number of THAs performed for femoral neck fractures in patients <65 years old. 21 A recent study conducted by Hochfelder et al in New York state revealed a trend toward increasing utilization of THA among a subset of femoral neck fracture patients younger than 70 years of age but an overall unchanged rate of THA for femoral neck fracture over time.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Recently published national registry data from Finland and Korea demonstrate an increasing utilization in THA over HA. 20 , 21 …”
Section: Introductionmentioning
confidence: 99%
“…With increasing average life expectancy, the incidence of these fractures is steadily increasing worldwide [ 1 3 ]. Internal fixation (IF) is the preferred treatment for undisplaced FNF [ 1 , 4 ]. Operative alternatives for FNFs in young adults are still being debated; the available options include prosthetic replacement (arthroplasty) and IF [ 1 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%